Efeito do derivado semissintético MC-D7, obtido da Moringa oleifera Lam., na inibição de aderência e de formação de biofilme por Streptococcus mutans : estudo In vitro - Freitas, Maria Tayara Marques de (2019)
In recent years, we have observed the growing interest of the pharmaceutical industry for the development of new antimicrobial drugs, especially those derived from natural sources, since the emergence of new drugs does not accompany the emergence of resistant microorganisms. Moringa oleifera Lam. has been shown a broad spectrum of biological activities, among them, anti-inflammatory, diuretic, antimicrobial, antioxidant, hypoglycemic, hypolipidemic, anticancer and antihypertensive action. Recent studies have observed the antitumor, anti-inflammatory and antinociceptive effect of the MC-D7, a semisynthetic derivative obtained from a benzylisothiocyanate isolated from the flower of M. oleifera Lam.. The antimicrobial effect of this derivative has not yet been evaluated. The objective of the present study is to evaluate the antimicrobial effect of MC-D7 as well as its effect on inhibition of adhesion and biofilm formation by Streptococcus mutans UA159 formed in vitro. To evaluate the antimicrobial activity of the compound in planktonic cells, a diffusion method was used in Agar and broth microdilution. As regards biofilm formation, the action of MC-D7 on the inhibition of adhesion and inhibition of biofilm formation by S. mutans was initially tested by the technique of quantification of the biomass by means of violet crystal staining with 24h formation. Additionally, the biofilm formation model on hydroxyapatite discs was also used to evaluate the effect of MC-D7 on the initial adherence of biofilm by S. mutans for 24h, 48h and 120h. The results showed that MC-D7 showed no antimicrobial effect at the concentrations tested (0,5 mg/mL to 0.0024 mg/mL). For the initial adhesion inhibition test, MC-D7 showed a significant inhibitory effect (p ≤ 0.05) for polystyrene plates at concentrations 0,5 mg/mL, 0.45 mg/mL and 0.4 mg/mL, and for hydroxylapatite disks at a concentration of 0,5 mg/mL, with 24 hours of biofilm formation. Therefore, it can be concluded that MC-D7 had an inhibitory effect on the adherence of S. mutans in the two substrates used, although other studies were necessary using higher concentrations of the drug in order to confirm its antimicrobial effect.